Detailed compared to ankle injuries among soccer players Foreign yards enclosed lounges and study - Hadi, Hassan; Mohammed, Ahmed (Journal of Physical Education, 2015)
The first Chapter included the introduction and the importance of research, as the sport injuries during the preparation and competitions - Stages, which is one of the most important problems that cause low level for the athletics, from these Injuries is the ankle joint injuries that occur to Soccer - players for Outdoor and Indoor Stadium. The aim of the research is to identify the proportion of ankle joint injuries and what are the reasons and the relationship between these Injuries for Outdoor and Indoor Stadium Soccer – players. It consisted (50) of the injured player. Chapter three contains the style of descriptive approach. In Chapter four the data was statistically significant treatment and reach the results of the research